Improved ionic and mechanical properties of ion-exchange membrane with an ionic silica network for high-performance ionic polymer-metal composites - Lee, Sangwoon; Choi, Young Eun; Lee, Jang Yeol; Yang, Taewook; Jho, Jae Young; Park, Jong Hyuk (한국공업화학회, 2023)
Ion-exchange membranes considerably affect the actuation of ionic polymer-metal composites (IPMCs) through ion movement under an applied voltage. To enhance the performances of IPMCs, previous stud-ies have increased the ionic content of the ion-exchange membrane, thereby improving its ionic conduc-tivity and water uptake. Although this increased ionic content enhances IPMC displacement, the increased water uptake diminishes IPMC stiffness, resulting in decreased IPMC blocking force. Therefore, a new approach is needed to resolve the trade-off between displacement and force. Here, we reinforced the Nafion membrane by forming a sulfonated polysilsesquioxane structure inside. The incorporation of this ionic silica network increased the total ion content of the membrane and included silica as a mechanically reinforcing filler. The force of the IPMC can be enhanced despite increased water uptake by the membrane. Therefore, IPMCs were obtained with improvements in displacement and blocking force. Comparison of the IPMCs with commercial Nafion films revealed similar displacement and superior force, demonstrating their applicability. These findings represent a breakthrough in enhanc-ing the actuation of IPMCs while resolving the trade-off between displacement and force. (c) 2023 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.